Increasing Climate Variability and Change Reducing the Vulnerability of Agriculture and Forestry - Salinger, James; Sivakumar, M.V.K.; Motha, Raymond P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
One of the major challenges facing humankind is to provide an equitable standard of living for this and future generations: adequate food, water and energy, safe shelter and a healthy environment. Human-induced climate change, and increasing climate variability, as well as other global environmental issues such as land degradation and loss of biological diversity, threaten our ability to meet these basic human needs. It is undisputed that the last two decades have been the warmest this century, and likely to be the warmest for the last 1000 years, sea level is rising, rain and snowfall patterns are changing. Arctic sea ice is thinning and the frequency and intensity of El-Niño events appear to be increasing. In addition, the frequency of extreme events is rising and many parts of the world have recently suffered major heat-waves, floods and droughts leading to significant loss of life and economic costs. This requires the global community to give urgent attention to addressing key issues. The range of adaptation options for agriculture and forestry is generally increasing because of technological advances, thus reducing the vulnerability of these systems to climate change. However, some regions of the world, particularly developing countries, have limited access to these technologies. Agriculture and forestry are currently not optimally managed with respect to today's natural climate variability. Decreasing the vulnerability of agriculture and forestry to increasing climatic variability will go a long way towards reducing the long-term vulnerability to climate change. This book represents a major step in assessing the science of climate variability and change, and their likely impacts on agriculture and forestry, with clear adaptation strategies required to reduce their vulnerability.
Increasing Climate Variability and Change: Reducing the Vulnerability -- Foreword -- Climate Variability and Change: Past, Present and Future - an Overview -- Impacts of Present and Future Climate Variability and Change on Agriculture and Forestry in the Arid and Semi-Arid Tropics -- Impacts of Present and Future Climate Variability on Agriculture and Forestry in the Humid and Sub-Humid Tropics -- Impacts of Present and Future Climate Variability on Agriculture and Forestry in the Temperate Regions: Europe -- Impacts of Present and Future Climate Change and Climate Variability on Agriculture in the Temperate Regions: North America -- Assessing the Consequences of Climate Change for Food and Forest Resources: A View from the IPCC -- Achieving Adequate Adaptation in Agriculture -- The Development of Seasonal and Inter-Annual Climate Forecasting -- Seasonal and Inter-Annual Climate Forecasting: The New Tool for Increasing Preparedness to Climate Variability and Change in Agricultural Planning and Operations -- Using Traditional Methods and Indigenous Technologies for Coping with Climate Variability -- Tomorrow's Forests: Adapting to a Changing Climate -- Management Strategies to Sequester Carbon in Agricultural Soils and to Mitigate Greenhouse Gas Emissions -- Climate, Communications, and Innovative Technologies: Potential Impacts and Sustainability of New Radio and Internet Linkages in Rural African Communities -- Role of Education and Training in Agricultural Meteorology to Reduce Vulnerability to Climate Variability -- Agrometeorological Research and Applications Needed to Prepare Agriculture and Forestry to 21st Century Climate Change -- Reducing Vulnerability of Agriculture and Forestry to Climate Variability and Change: Workshop Summary and Recommendations.
Keywords: ENVIRONMENTAL SCIENCES; METEOROLOGY; AGRICULTURE; FORESTS AND FORESTRY; CLIMATIC CHANGES; ENVIRONMENTAL MANAGEMENT; ENVIRONMENT; CLIMATE CHANGE; ENVIRONMENTAL MANAGEMENT; METEOROLOGY/CLIMATOLOGY.; AGRICULTURE; FORESTRY MANAGEMENT